Insatisfacao corporal, comprometimento psicológico ao exercício e comportamento alimentar em jovens atletas de esportes estéticos - de Sousa Fortes, L.; Mockdece Neves, C.; Fernandes Filgueiras, J.; Sousa Almeida, S.; Caputo Ferreira, M. E. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
The prevalence of inadequate eating behavior is high in athletes. However, little is known about the factors that affect this phenomenon in this population. The aim of this study was to evaluate the association of body dissatisfaction and level of psychological commitment to exercise (LPCE) with inadequate eating behavior in young athletes from aesthetic sports. Forty-seven female athletes practicing aesthetic sports (artistic gymnastics, synchronized swimming and high diving), ranging in age from 12 to 16 years, participated in the study. The Eating Attitudes Test (EAT-26), Body Shape Questionnaire (BSQ) and Commitment to Exercise Scale (CES) were used to evaluate the risk behavior for eating disorders, body dissatisfaction and LPCE, respectively. Skinfold thickness was measured to calculate body fat percentage of the athletes. The results revealed a significant association between body dissatisfaction and eating behavior and between LPCE and risk behavior for eating disorders. Multiple linear regression analysis showed that all variables, except for fat percentage, influenced the eating behavior of young athletes. This analysis also indicated an influence of body fat percentage and body dissatisfaction on CES scores. It was concluded that body dissatisfaction and LPCE are factors that predispose to risky eating behaviors in athletes from aesthetic sports.